Pengaruh Pendidikan Keuangan Di Keluarga, Sosial Ekonomi Orang Tua, Dan Pengetahuan Keuangan Terhadap Manajemen Keuangan Pribadi Mahasiswa Fakultas Ekonomi Universitas Pasir Pengaraian - Ingga Liamsi; Fefti Yulian Mela; Nurhayati (Jurnal Ilmiah Raflesia Akuntansi, 2026)
A total of 150 active students at the Faculty Economics Pasir Pengaraian University studying financial management, class of 2022, were given a questionnarie to colect data. The aim was to identify and analyze the influence of family financial education, parental socioeconomic and financial knowledge on students’s personal financial management. The variables were tested using SPSS version 24. The research findings indicate that family financial education (X1) and financial knowledge (X3) have a positive and significant effect on personal financial management (Y), parental socioeconomic (X2) has a negative and significant effect on personal financial management (Y), and simultaneously, the variables of family financial education (X1), parental socioeconomic (X2), and financial knowledge (X3) have a positive and significant effect on personal financial management (Y).